SUCCESSES AND CHALLENGES IN TEACHING CODING AND ROBOTICS IN GRADE 7-9 (SENIOR PHASE) IN PILOT SCHOOLS: LIVED TEACHERS’ EXPERIENCES - Gcizelela, Ngcobo Wiseman (Veredas do Direito, 2026)
The incorporation of Coding and Robotics (C&R) into the Grades 7–9 (Senior Phase) curriculum in South Africa aimed to equip learners with essential skills required to thrive in the Fourth Industrial Revolution, including computational thinking, problem-solving, creativity, and collaboration. Although successes in implementing and teaching C&R had been reported, the initiative continued to face substantial obstacles. This study explored South African Senior Phase teachers’ experiences in implementing and teaching the newly approved Curriculum and Assessment Policy Statement (CAPS) in pilot schools. Using a qualitative case study framed within the Technological Pedagogical Content Knowledge (TPACK) theory, embedded in the interpretivist paradigm, the study employed interviews, document analysis, and observations to generate and collect data from purposively selected Senior Phase C&R teachers. The data were then thematically analysed. The findings illuminated successes (changes in teacher attitudes, increased teacher engagement, and parental support), as well as constraints (staff capacity, knowledge and understanding of C&R, infrastructure, and institutional and administrative barriers) and enablers [coaching, Professional Learning Communities (PLCs), unplugged-to-plugged learning sequences, and the ethical use of generative AI]. These findings offered actionable recommendations for the successful and equitable implementation and teaching of C&R.